The International Evidence on Income Distribution in Modern Economies: Where Do We Stand? - Timothy Michael Smeeding; Peter Thomas Gottschalk (Luxembourg Income Study (LIS), 1995)
Interest in cross-national comparisons of personal income distributions, low relative incomes, and income inequality in general has grown dramatically during the past five years. This paper summarizes and provides limited updates on a small part of what was learned in a large study undertaken for the OECD by Atkinson, Rainwater and Smeeding, and a subsequent review article by Gottschalk and Smeeding. It also adds recent material for Central and Eastern European nations based on the work of Torrey, Smeeding and Bailey as well as for Taiwan. The paper summarizes the differences in both levels and trends in income inequality across countries.
Keywords: 330